Secretin receptor-deficient mice exhibit altered circadian rhythm in wheel-running activity. (23rd March 2020) - Sugiyama, Mizuki; Nishijima, Ichiko; Miyazaki, Shota; Nakamura, Takahiro J.
Abstract: In mammals, the timing of behavior and physiological activity is controlled by the suprachiasmatic nucleus (SCN) in the hypothalamus. Incidentally, secretin is a peptide hormone that promotes digestive activities and regulates water reabsorption. In recent studies, exogenous administration of secretin has been reported to induce secretion of oxytocin in the supraoptic nucleus of the hypothalamus and modulate social behavior. These results indicate that secretin is involved in the neural network that controls social behavior and plays important roles in the central nervous system. In the present study, we investigated the effects of secretin on circadian rhythms, by assessing circadian rhythms during wheel-running behavior in secretin receptor-deficient ( Sctr −/− ) mice. Male adult wild-type (WT) and Sctr -/- mice were housed in separate cages containing a wheel. Every minute of the wheel-running activity was monitored during the normal light-dark (LD) cycle (12:12 h) and in constant darkness (DD). Significant differences were observed in the free-running period between the WT and Sctr −/− mice. However, no significant differences were observed in the daily wheel-running revolutions between WT and Sctr −/− mice, in the LD and DD conditions. Moreover, the ratio of the daily activity phase to the rest phase (α/ρ) was significantly smaller in Sctr −/− than that in WT mice in the DD condition. Secretin receptors were expressed in the SCN cells. These findings suggest that secretin receptors are involved in the central circadian clock in the SCN and the circadian system in general.